New area efficient memristor realizations. (May 2021) - Yildiz, Hacer Atar
Abstract: In this paper, new active-only memristor emulator circuits based on only one active element and one single transistor are proposed. These circuits use intrinsic capacitors of the MOS transistors without using any external passive components. These types of circuits have some important advantages over the integrated circuit, such as low occupied chip area and electronic tuning capability. However, memristor emulator circuits suffer from limited operation frequency range. To address this issue, a new modification technique used to extend circuits' operating frequency range is introduced. Furthermore, the proposed memristor emulators can also be used to implement basic filtering functions. The main nonidealities are studied and proper operations of these circuits are provided via Spectre Simulation results in 0.18 ​μm Cadence design tool.